Relationship between product factors, advertising, and purchase intention of halal cosmetic - Hussin, Siti Rahayu; Hashim, Haslinda; Raja Yusof, Raja Nerina; Alias, Nurul Najmi (Universiti Putra Malaysia Press, 2013)
More customers are aware of Halal products, especially among Muslim customers living in multi-religious societies such as Malaysia. The trend is customers are also becoming more conscious about the permissibility (Halal) of a wide range of products ranging from food, financial and non-financial products, to tourism and health products. This apparently has prompted marketers operating in food, cosmetics, and pharmaceutical products to revise their strategies. The purpose of this paper is to investigate the relationships between five product factors; namely, brand, price, quality, ingredients and labelling and purchase intention of Halal cosmetic and toiletry products. The study also examined the role of advertising in the relationship between product factors and purchase intention. For this purpose, a structured questionnaire was designed based on items adapted from previous studies. Data were collected from 200 adult Muslim respondents using a convenience sampling method. Pearson Correlation and multiple regression analysis were used to test the proposed model. The results indicated that all product factors are significantly correlated with purchase intention. The results further indicate that advertising is a mediator for price-purchase intention relationship, but not a mediator to other product factors-purchase intention relationships. This study provides insights into how consumers behave in purchasing Halal products, given five product factors of brand, price, quality, ingredients and labelling. It is argued in this research that the presence of advertising may not change the intention to purchase Halal products but price may influence purchase intention.